Konflik batin pada tokoh Rengganis dalam novel Hati Suhita karya Khilma Anis berdasarkan pendekatan psikologi sastra - Mardiah, Nazifatul (Maliki Interdisciplinary Journal, 2026)
This study examines the inner conflicts experienced by Ratna Rengganis, a central character in Khilma Anis’s novel Hati Suhita, through the perspective of literary psychology using Abraham Maslow’s hierarchy of needs. Hati Suhita presents a complex relational dynamic without introducing an antagonistic character; instead, it highlights the psychological struggles of its characters, particularly Rengganis. She is portrayed as a loyal, self-sacrificing, and emotionally mature woman who is confronted with painful realities such as separation, family pressure, and an unattainable love. The findings of this research show that Rengganis’s inner conflicts involve sadness, disappointment, confusion, loss, inferiority, acceptance, and the determination to rise again. These conflicts emerge as consequences of unmet psychological needs as described by Maslow, especially the needs for love, safety, self-esteem, and self-actualization. Through an in-depth analysis of selected excerpts from the novel, this study demonstrates that Rengganis’s psychological journey reflects the struggle of a woman who ultimately attains emotional maturity through sincerity and resilience. This research is expected to contribute to literary psychological studies, particularly those exploring the dynamics of female characters’ inner conflicts in contemporary Indonesian literature.